EVALUATION OF THE EFFECTS OF ILLUMINATION, TEMPERATURE AND PAINTING FINISH IN PSP TECHNIQUE - Costa, R. S.; Avelar, A. C.; Falcao Filho, J. B. P. (Revista de Engenharia Térmica, 2013)
This paper reports the results of global pressure measurements on a NACA0012 profile, obtained with the Pressure Sensitive Paint technique (PSP), and compares them with conventional pressure tap measurements with the purpose of analyzing the influence of parameters as illumination efficiency and temperature variation of the air flow in the accuracy of the PSP experimental results. The experimental measurements were conducted in the Pilot Transonic Wind Tunnel (TTP) of the Instituto de Aeronáutica e Espaço (IAE) for Mach number values of 0.4, 0.6 and 0.8. The experiments showed that in a carefully prepared experiment, under appropriated operational conditions, and rigorous adjustments of the PSP components, the obtained results can be accurate. Moreover, even when the influence of temperature is significant and the illumination condition is not ideal, it was possible to estimate well the impact caused in the pressure distribution over the model surface.